Inhibition of phosphorylated Ser473‐Akt from translocating into the nucleus contributes to 2‐cell arrest and defective zygotic genome activation in mouse preimplantation embryogenesis. (23rd March 2016) - Chen, Junming; Lian, Xiuli; Du, Juan; Xu, Songhua; Wei, Jianen; Pang, Lili; Song, Chanchan; He, Lin; Wang, Shie
Abstract : Phosphorylated Ser473‐Akt (p‐Ser473‐Akt) is extensively studied as a correlate for the activity of Akt, which plays an important role in mouse oogenesis and preimplantation embryogenesis. However, little progress has been made about its effect on the mouse zygotic genome activation (ZGA) of 2‐cell stage in mouse preimplantation embryos. In this study, we confirmed its localization in the pronuclei of 1‐cell embryos and found that p‐Ser473‐Akt acquired prominent nucleus localization in 2‐cell embryos physiologically. Akt specific inhibitors API‐2 and MK2206 could inhibit the development of mouse preimplantation embryos in vitro, and induce 2‐cell arrest at certain concentrations. 2‐cell embryos exposed to 2.0 μmol/L API‐2 or 30 μmol/L MK2206 displayed attenuated immunofluorescence intensity of p‐Ser473‐Akt in the nucleus. Simultaneously, qRT‐PCR results revealed that 2.0 μmol/L API‐2 treatment significantly downregulated the mRNA pattern of MuERV‐L and eIF‐1A, two marker genes of ZGA, suggesting a defect in ZGA compared with that of control group. Collectively, our work demonstrated the nuclear localization of p‐Ser473‐Akt during major ZGA, and Akt specific inhibitors API‐2 and MK2206 which led to 2‐cell arrest inhibited p‐Ser473‐Akt from translocating into the nucleus of 2‐cell embryos with defective ZGA as well, implying p‐Ser473‐Akt may be a potential player in the major ZGA of 2‐cell mouse embryos. Abstract : The localization of p‐Ser473‐Akt in the nucleus of two‐cell embryos is highly associated with ZGA, and Akt specific inhibitors API‐2 and MK2206 leading to 2‐cell arrest and defective zygotic genome activation is related to the inhibition of p‐Ser473‐Akt translocating into the nucleus in 2‐cell embryos.